2018
DOI: 10.1111/jocd.12476
|View full text |Cite
|
Sign up to set email alerts
|

Filler migration and extensive lesions after lip augmentation: Adverse effects of polydimethylsiloxane filler

Abstract: Polydimethylsiloxane (PDMS), also called liquid silicone, belongs to a group of polymeric compounds that are commonly referred to as silicones. These filling agents have been used as injectable filler for soft tissue augmentation. There are limited experiences about management of the severe complications related to filler migration associated with PDMS injection. We present a 35-year-old female with severe erythema, edema over her cheeks and neck, and multiple irregularities following cosmetic lip augmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
12
0
5
Order By: Relevance
“…Some of the special polymers which can crosslink with HA are silicon-based synthetic polymers such as PDMS. Although pure silicon is a popular filler with considerable properties such as high flexibility, high gas permeability, non-toxicity, and biocompatibility, it may cause undesirable symptoms [28]; for instance, the filler makes up of PDMS has been associated with migration, overcorrection, and deformation in the treatment place [29]. Nevertheless, a study on 95 patients who received silicon oil emulsified with HA (without any chemical bond formation between them) during the 2-years medical following-up, showed very slight complications such as some small and temporary nodules, with no observation of granulomas or filler migration [30].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the special polymers which can crosslink with HA are silicon-based synthetic polymers such as PDMS. Although pure silicon is a popular filler with considerable properties such as high flexibility, high gas permeability, non-toxicity, and biocompatibility, it may cause undesirable symptoms [28]; for instance, the filler makes up of PDMS has been associated with migration, overcorrection, and deformation in the treatment place [29]. Nevertheless, a study on 95 patients who received silicon oil emulsified with HA (without any chemical bond formation between them) during the 2-years medical following-up, showed very slight complications such as some small and temporary nodules, with no observation of granulomas or filler migration [30].…”
Section: Introductionmentioning
confidence: 99%
“…Complications reported in the literature include filler migration, irregularities. 7 A study published by the Department of Dermatology, University of Miami, Florida, in 2012 analyzed the results of 95 patients who received S1000 emulsified with hyaluronic acid as dermal filler for various treatment areas including acne scars, glabella, nasolabial folds, liquid rhinoplasty, cheek, chin, and lip augmentations. The authors reported minimal complications as small nodules that resolved by massage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The attempt to have cosmetic facial surgeries has been increasing over the past years. Fillers for tissue enhancement are acquiring great popularity (11). For this purpose, the filler injection is used in the lip, especially the upper lip (12)(13)(14)(15).…”
Section: Dear Editormentioning
confidence: 99%
“…Liquid silicone which is also known as polydimethylsiloxane relates to a group of polymeric compounds that are frequently called silicones. These fillers have been applied as injectable filling agents for soft tissue enhancement and cosmetic lip augmentation (11). In a study, recently severe edema, erythema over cheeks and neck, and several irregularities were reported following lip augmentation with polydimethylsiloxane (11).…”
Section: Dear Editormentioning
confidence: 99%